2022
DOI: 10.1101/2022.04.19.22273931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prevalence of Mental Health Disorders in people with HIV and the effects on the HIV Care Continuum

Abstract: ObjectiveTo describe the prevalence of diagnosed depression, anxiety, bipolar disorder, and schizophrenia in people with HIV (PWH) and the differences in HIV care continuum outcomes in those with and without mental health disorders (MHD).DesignObservational study of participants in the NA-ACCORD.MethodsPWH (≥18 years) contributed data on prevalent schizophrenia, anxiety, depressive, and bipolar disorders from 2008-2018 based on ICD code mapping. MH multimorbidity was defined as having ≥ 2 MHD. Log binomial mod… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The prevalence of having depression, anxiety, stage ≥3 CKD, dyslipidemia, type 2 diabetes, hypertension, cancer (all types), myocardial infarction (MI), and ESLD (at or prior to ART initiation) was estimated at the time the simulated person initiated ART ( Figure 1 ). 24,30,3941 Incidence of each comorbidity was estimated as a function of age, CD4 at ART initiation (cells/μL), time since ART initiation, disengagement from care, change in BMI in the first 2 years after ART initiation, BMI 2 years after ART initiation, smoking, HCV co-infection, and the presence of the other comorbidities for simulated persons in the years after ART initiation ( Supplement Table S2 ). Finally, mortality was estimated for simulated persons as a function of individual-level attributes, existing risk factors, and present comorbidities, and was estimated separately for those (1) engaged and (2) disengaged from care (≥2 years without CD4 or HIV RNA measurement) and in each of the 15 sub-groups using observed NA-ACCORD data from 2009-2017 ( Supplement Table S3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of having depression, anxiety, stage ≥3 CKD, dyslipidemia, type 2 diabetes, hypertension, cancer (all types), myocardial infarction (MI), and ESLD (at or prior to ART initiation) was estimated at the time the simulated person initiated ART ( Figure 1 ). 24,30,3941 Incidence of each comorbidity was estimated as a function of age, CD4 at ART initiation (cells/μL), time since ART initiation, disengagement from care, change in BMI in the first 2 years after ART initiation, BMI 2 years after ART initiation, smoking, HCV co-infection, and the presence of the other comorbidities for simulated persons in the years after ART initiation ( Supplement Table S2 ). Finally, mortality was estimated for simulated persons as a function of individual-level attributes, existing risk factors, and present comorbidities, and was estimated separately for those (1) engaged and (2) disengaged from care (≥2 years without CD4 or HIV RNA measurement) and in each of the 15 sub-groups using observed NA-ACCORD data from 2009-2017 ( Supplement Table S3 ).…”
Section: Methodsmentioning
confidence: 99%
“…1). 24,30,[39][40][41] Incidence of each comorbidity was estimated as a function of age, CD4 at ART initiation (cells/µL), time since ART initiation, disengagement from care, change in BMI in the first 2 years after ART initiation, BMI 2 years after ART initiation, smoking, HCV co-infection, and the presence of the other comorbidities for simulated persons in the years after ART initiation (Supplement Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…As for PLWHA, anxiety disorders are one of the most common psychiatric illnesses in HIV-associated mental disorders (7,8). Overall, different studies have reported the incidence of anxiety disorders among people living with HIV/AIDS ranging from 0.6% to 68.2% (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In the general population, anxiety is a risk factor for cognitive impairment (19), it can adversely affect the brain (20), and also it has a negative impact on disorders other than those related to the neuropsychiatric system (21).…”
Section: Introductionmentioning
confidence: 99%